PERAN GURU AKIDAH AKHLAK DALAM MEMBINA ETIKA BERPAKAIAN SISWA KELAS VII DI MTs AL-MA’ARIF 02 SINGOSARI MALANG - Siti Ani Masruroh; Rosichin Mansur; Moh Muslim (VICRATINA, 2021)
The moral aqidah teacher has a goal, namely to make students become human beings who are faithful, devoted, independent, creative and have noble character. In this modern era, many students wear tight clothes, wear revealing clothes, wear clothes but their nakedness is still visible. The position of the researcher here is as a key instrument that collects data by themselves though observation, interviews, and documentation. The approach used in this research is descriptive qualitative approach and the type of research is case study. The result of the research that has beeb carried out are that at MTs Al- Ma’arif 02 Singosari Malang, the planning of teachers of moral aqudah in fostering dress ethics is that the teacher prepares himself as a supporter in carrying out ethicas guidance to students, beside that the teacher only support the existing regulation by way of do crosschecks every morning. Then for the application of dress ethics for class VII students, many students use uniforms according to schedule, many students wear polite and polite clothes, then for the role of teachers of moral aqidah in fostering dress ethics for class VII students in this scholl, there are three roles that teachers have, including teachers as supervisors, teachers as educators, and teachers as models or role modelas. Kata Kunci: The role of the teacher of moral aqidah, Fostering, Dress etiquette.